Étude de cas d'une pratique enseignante de lecture d'album en cycle 3 : de l'intention au réalisé - Nicole Audoin-Latourte (Nantes Université, 2015)
This article is based on the case study of a session in literature led by a teacher in year 6, from a satirical album. It tries to understand the teacher's activity in the field of didactics of literature, and in the exploitation of the link between the text and the picture, in a catchy yet complex album. The article analyzes how the teacher's intentions in children's literature, expressed in interviews during the preparation of the session, or after the session, are reflected and achieved or not in the classroom. It points out the difficulty to take into account the students' learning abilities in both the reported intentions and the actual practice observed.